2005
DOI: 10.1037/0033-2909.131.6.898
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal Behavior and the Vertical Dimension of Social Relations: A Meta-Analysis.

Abstract: The vertical dimension of interpersonal relations (relating to dominance, power, and status) was examined in association with nonverbal behaviors that included facial behavior, gaze, interpersonal distance, body movement, touch, vocal behaviors, posed encoding skill, and others. Results were separately summarized for people's beliefs (perceptions) about the relation of verticality to nonverbal behavior and for actual relations between verticality and nonverbal behavior. Beliefs/perceptions were stronger and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
625
1
19

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 677 publications
(718 citation statements)
references
References 183 publications
36
625
1
19
Order By: Relevance
“…Furthermore, though power and status are distinct constructs (Emerson, 1962;Fiske, 2010;Goldhamer & Shils, 1939;Hall et al, 2005;Henrich & Gil-White, 2001;Ridgeway & Walker, 1995;Sachdev & Bourhis, 1985) in real world settings it is likely that power and status will be highly correlated McGuire, Brammer, & Raleigh, 1986).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Furthermore, though power and status are distinct constructs (Emerson, 1962;Fiske, 2010;Goldhamer & Shils, 1939;Hall et al, 2005;Henrich & Gil-White, 2001;Ridgeway & Walker, 1995;Sachdev & Bourhis, 1985) in real world settings it is likely that power and status will be highly correlated McGuire, Brammer, & Raleigh, 1986).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Nonverbal behavior may serve several functions, including providing information, regulating interactions, expressing intimacy, and exerting social control (Patterson, 1982). More than 15 separate meta-analyses in psychology and related fields in the past decade have documented pertinent research (e.g., DePaulo et al, 2003;Elfenbein & Eisenkraft, 2010;Hall, Coats, & LeBeau, 2005;Riggio & Riggio, 2002).…”
Section: Nonverbal Behavior As a Key Component Of The Retail Environmentmentioning
confidence: 99%
“…A distinctive pattern of nonverbal behaviors characterizes high-status persons. A recent meta-analysis of this research stream identified facial expressiveness, greater bodily openness, and smaller interpersonal distances as behaviors that are characteristic of higher status persons (Hall, Coats, & LeBeau, 2005). From a complementarity perspective, customers' politeness behavior should be associated with salespeople's high-status behaviors (or retail atmosphere cues), in which case politeness behavior by the customer might be obscuring his or her true feelings from the retailer or salesperson.…”
Section: Social Status: Politeness As An Alternate Approach To Persuamentioning
confidence: 99%
“…Because many cultures are organized by social hierarchy, others' social status affords perceivers valuable information and determines behavioral consequences. It is cued by signals of dominance (marking higher status) and signals of subordination (marking lower status), which are conveyed effortlessly by bodily expressions (Hall et al, 2005). Although these cues are recognized with considerable consistency across cultures (e.g., Bridge et al, 2007), cultures can greatly differ in how they assign value to these cues.…”
Section: Values In Perception: Dominance and Subordinationmentioning
confidence: 99%
“…Beyond recognizing others' emotions, we often see their social status as well, as it is readily revealed by the face and body (Hall et al, 2005). Because many cultures are organized by social hierarchy, others' social status affords perceivers valuable information and determines behavioral consequences.…”
Section: Values In Perception: Dominance and Subordinationmentioning
confidence: 99%